Jesus Christ: a guide for study and devotion - McGrath, Alister E. (The heart of Christian faith series, 2014)
Jesus of Nazareth: the turning point -- Jesus of Nazareth: assembling the big picture -- Incarnation: the word became flesh -- Atonement: putting things right -- Jesus of Nazareth and the life of faith